Investigating kinetics in the freestyle flip turn push-off - Lyttle, A. D.; Blanksby, B. A.; Elliott, B. C. (Journal of Applied Biomechanics, 1999)
Thirty experienced male swimmers with body types ± 1 SD of the mean of selected body form parameters reported for elite male swimmers were recruited for the study. During three freestyle flip turns, selected kinetic, hydrodynamic, and kinematic variables of the push-off following a flip turn were recorded. Kinetics were recorded via a 2D vertically mounted forceplate that recorded peak push-off force and total impulse. The acceleration of each swimmer`s center of gravity and wall exit velocity were calculated from underwater videography. Hydrodynamic peak drag force and drag impulse were calculated from the kinetic and kinematic data using a derivative of Newton`s second law. A stepwise regression yielded peak drag force, peak propulsive force, and push-off time in the final regression equation (R = 0.80; R2 = 0.64). Beta values indicated that the peak drag force carried the highest weighting of the three variables. The results of the stepwise regression indicated that a combination of a low peak drag force high peak propulsive force, and increased wall push-off time produced the fastest final push-off velocity.